AN GEOLOGICAL OVERVIEW OF GLACIAL ACCUMULATION AND EROSIONAL OCCURRENCES AT THE VELEBIT AND THE BIOKOVO MTS., CROATIA - Josipa Velić; Ivo Velić; Dubravka Kljajo; Ksenija Protrka; Hrvoje Škrabić; Zlatko Špoljar (Rudarsko-geološko-naftni Zbornik, 2017)
Numerous accumulation and erosional forms originating from the activity of small valley glaciers or cirque glaciers occur in the highest mountains in Croatia: Velebit (1757 m) and Biokovo (1762 m). They were produced during the Upper Pleistocene, in the Würm glacial stage of the Alpine classification. Accumulation forms comprise ground, terminal and recessional moraines, drumlins, eskers, glacial erratics and glaciofluvial and glaciolacustrine sediments. Single ridge eskers are often associated with areas of kame and kettle topography. Among erosional occurrences roche moutonnée (sheepback rocks), U-shaped valleys ranging in size from meso-macro, arêtes, hanging valleys, meso-sized cirques, kettles, and striations were noted. In Croatian Dinarides such forms in most cases occur between 900 and 1400 meters altitude. During the early to middle Würm glacial maximum, the snow line was above 900 m, perhaps even above 1000 m altitude, and sea levels were 120 meters lower than at present day. Considering the features of the present relief, ice cover was probably 200 to 300 m thick. Features of drumlins, eskers and kettles point to warm-based glaciers. The drumlins are small – up to 100 meters long and 50 meters wide, with the most common long axis ranging orientation from 130o – 310o. The near total absence of platy clasts, as well as their stratigraphic affiliation, largely reflects features of source rocks.